Media Framing on Hijab in the Western Media and Societal Challenges for Muslim Women: A Public Policy Discourse - Ghousia Tasneem; Dr. Syed Shameel Ahmed Quadri; Dr. Aurangzeb; Dr. Shamaila Athar; Athar Azeem; Dr. Shahzad Sadiq Faridi; Dr. Muhammad Nasir Mahmood; Dr. Hafiz Muhammad Idrees (Al-Qanṭara, 2023)
: This study looks into the media framing of the Hijab (Muslim headscarf) in Western media and its significant effects on Muslim women living in Western societies. The hijab has received a lot of discussion and attention in Western media. This study thoroughly analyzes academic literature, media sources, and empirical studies to show how Western media portray the hijab. It also examines the social issues Muslim women confront due to these media framings.The analysis demonstrates the intricate interaction of Western media's frames to discuss the hijab. Negative framing frequently reinforces stereotypes by painting Muslim women who wear the hijab as oppressed, subservient, and with potential security risks. Some media outlets unintentionally encourage Islamophobia by linking the hijab to extremism. A positive frame recognizes the hijab as a sign of empowerment and religious freedom.These media framings present significant and varied socioeconomic challenges. Muslim women who wear the hijab face stigmatization, discrimination, and career difficulties; many also experience verbal and physical harassment due to the hostile environment fostered by inaccurate media portrayals. Additionally, repeated criticism of one's looks and identity can significantly negatively impact one's self-esteem and sense of self, frequently leading to alienation and internal turmoil. These issues are made more difficult by the media's scant exposure of varied voices and viewpoints, reinforcing stereotypes and muting the voices of Muslim women who wear the hijab.This study emphasizes the significance of media accountability and ethical reporting. The media must fairly and objectively cover the hijab without sensationalism or unfavorable preconceptions. Supporting varied viewpoints and views in the media can help give a more accurate representation of Muslim women's experiences and promote inclusion and tolerance in Western society. Muslim women must be empowered to share their stories and experiences to challenge and reshape prevalent preconceptions and misconceptions regarding the hijab. The study recommends a deliberate effort to advance openness, tolerance, and understanding in Western society while also recognizing the autonomy and variety of Muslim women who choose to wear the hijab.